THE IMPLEMENTATION OF PROBLEM-BASED LEARNING TO TEACH SPEAKING HORTATORY EXPOSITION TEXT TO THE ELEVENTH GRADERS OF SMA MUHAMMADIYAH 2 SURABAYA (RETAIN, 2016)
THE IMPLEMENTATION OF PROBLEM-BASED LEARNING TO TEACH SPEAKING HORTATORY EXPOSITION TEXT TO THE ELEVENTH GRADERS OF SMA MUHAMMADIYAH 2 SURABAYA Amalia Liesya H. English Education, Language and Arts, State University of Surabaya amaliah1@mhs.unesa.ac.id Dr. H. Aswandi, M. Pd English Education, Language and Arts, State University of Surabaya aswandi@unesa.ac.id Abstrak Semenjak tujuan pembelajaran bahasa Inggris membuat pembelajar dapat berbicara dengan baik, penelitian ini berkaitan denganpengajaran berbicara teks eksposisi hortatori dengan mengimplementasikan problem-based learning. Problem-based learning sendiri adalah salah satu model pembelajaran yang disarankan dalam kurikulum 2013 dimana model pembelajaran ini menyediakan permasalahan dunia yang harus dipecahkan murid. Penelitian ini bertujuan untuk mengetahui proses belajar mengajar yang menggunakan problem-based learning di kelas dan respon siswa terhadap pengimplementasian model pembelajaran ini. Penelitian ini menggunakan deskripsi kualitatif sebagai metodologi penelitian. Peserta penelitian yang dipilih untuk penelitian ini adalah seorang guru bahasa Inggris dan 15 siswa kelas XI. Data penelitian diperoleh dengan mendakan observasi dan memberi kuesioner kepada siswa. Berdasarkan analisis dari serangkaian observasi, pencatatan, dan kuesioner, dapat dinyatakan bahwa model pembelajaran problem-based learning dapat diimplementasikan untuk mengajar berbicara teks eksposisi hortatori. Kegiatan pembelajaran berhasil mencakup seluruh langkah problem-based learning dan langkah kurikulum 2013. Hasil kuesioner juga menunjukkan respon positif terbukti saat murid tertarik dan menikmati kegiatan pembelajaran. Kata Kunci: problem-based learning, berbicara, teks eksposisi hortatori. Abstract Since the goal of English learning is making the learners able to speak well, this research focuses on teaching speaking hortatory exposition text by implementing problem-based learning. Problem-based learning itself is one of suggested learning model of 2013 Curriculum which provides students real world problems to be solved. This research is about to discover the teaching learning process by implementing problem-based learning in class and the students’ responses toward it. This research used descriptive qualitative as the research design. An English teacher and 15 eleventh grade students were chosen as the participants of the study. The data were obtained by conducting observation and giving questionnaire to the students. Based on the analysis of set of observations, field notes, and questionnaire, it is confirmed that problem-based learning can be implemented to teach speaking hortatory exposition text. The teaching and learning activities successfully covered the stages of problem-based learning and stages of 2013 curriculum. The result of questionnaire also showed positive response since the students were attracted and enjoyed the teaching learning activities. Keywords: Problem-based learning, speaking, hortatory exposition text.